EFEKTIVITAS PERMAINAN IMAJINASI TERHADAP PENGENALAN GEOMETRI ANAK USIA DINI KOBER SHIRATUN DHAUU’N CIPATAT BANDUNG BARAT - Eni Rohaeni; Andrisyah Andrisyah (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2018)
The problem in the field is that they are not interested and children are not happy about learning in the classroom. Especially in learning to know geometric shapes. This is shown by not paying attention to the teacher who is explaining in front of the class. Almost all children are seen to be passive towards learning activities. In this study, researchers will explore the introduction of geometry at an early age of 5-6 years. The method in this study was carried out with a quasi-experimental with the data source being group B Kober Shiratun Dhauun children, amounting to 22 people, and divided into two groups. The results of the study prove that the imagination play method can arouse enthusiasm and increase understanding of geometry in children. It is seen that children are more enthusiastic and children become conducive atmosphere. From the data obtained on the N Gain results, the average value of experiment and control where the average value at the beginning of learning (pretest) of each class and at the end of learning (posttest) the average value of the experiment became 36.21 and control 28.64. Based on the results of the study, the introduction of geometry with the method of imagination play is more fun and interesting for children, so they are more motivated to study hard and passionately.